Occupational risk factors for low back pain among drivers of three-wheelers in Sri Lanka. (September 2015) - Noda, Misa; Malhotra, Rahul; DeSilva, Vijitha; Sapukotana, Pasindu; DeSilva, Asela; Kirkorowicz, Jacob; Allen, John; Østbye, Truls
Abstract : Background: Approximately 5% of all households in Sri Lanka operate a three-wheeler as their primary source of income. However, very little is known about the occupational health risks associated with driving these vehicles. Objectives: The aim of this study was to assess occupational risk factors, including the number of hours worked associated with the 4-week prevalence of low back pain (LBP) among drivers of three-wheelers. Methods: Questionnaires were administered to 200 full-time drivers of three-wheelers from the Galle District in Sri Lanka. Occupational, psychological, socio-demographic, lifestyle, and anthropometric variables were collected. Univariate and multivariate analysis were used to investigate the correlation between occupational risk factors of the prevalence of LBP. Results: 15·5% of respondents reported experiencing LBP in the previous 4 months. Univariate analysis revealed that the number of hours worked per week, feeling pressure to compete with other drivers, and perceived stress scale scores were significantly associated with the 4-week prevalence of LBP. Multivariate analysis found that the number of hours worked per week and engine type were significantly associated with LBP. Conclusions: LBP is common among drivers of three-wheelers in Sri Lanka. Long work hours and two-stroke engines were significantly associated with LBP. Results from this study point towards a role for educational, behavioral health, and policy interventions to help prevent and reduce LBP among these drivers.